Feasible use of recycled alumina combined with recycled aggregates in road construction. (20th January 2019) - López-Alonso, M.; Martinez-Echevarria, M.J.; Garach, L.; Galán, A.; Ordoñez, J.; Agrela, F.
Highlights: A laboratory study of materials based on the addition of Aluminum Waste are presented. RCA and MRA with AW mixtures could be used in unbound road layers. Using AW and RCA and MRA mixtures in construction is a good recycling alternative. Abstract: Several studies have applied recycled aggregates (RA) in road layers and demonstrated appropriate results. In general, RA can be one of two types: recycled concrete aggregates (RCA) or mixed recycled aggregates (MRA), each of which has lower density, higher water absorption, and lower mechanical strength than natural aggregates (NA). Alumina waste (AW), obtained from the process of aluminum refinement, could be mixed with RA in order to improve its properties, such as compaction and bearing capacity, for application in road construction. Few studies have investigated the use of AW with RA in civil constructions. This paper presents the results of a laboratory study of different materials based on the addition of AW to RCA and MRA. In the experiment, the mechanical behaviors and microstructural properties of RCA, MRA, and mixes of RCA or MRA with AW were compared. Different specimens of unbound recycled mixtures demonstrated increased resistance properties, and the formation of new cement hydrated particles was observed in these novel mixtures. The properties of the mixtures of RCA and MRA with AW suggest that these recycled materials can be used in unbound road layers to improve the long-term mechanical behavior.